Effect of the third dose of BNT162b2 COVID-19 mRNA vaccine on anti-SARS-CoV-2 antibody levels in healthcare workers. Issue 2 (9th January 2023) - Tanaka, Hidenori; Mukai, Junji; Kushibiki, Kenichi; Mizushima, Sayuri; Maeda, Kyoko; Fujimoto, Yuko; Sawada, Ryugo; Oda, Manabu; Okuda, Hiroshi; Yamaki, Mayumi; Hashiguchi, Shin; Kawai, Ichiro; et al.
Highlights: Anti-SP antibody titer compared after second and third doses of the BNT162b2 vaccine. Study conducted on healthcare workers directly exposed to COVID-19 patients. Anti-SP IgG titer decreased slowly after second dose of the vaccine. Peak IgG titer 4.1-fold higher after the third dose than after first and second doses. Adverse events following immunization were generally mild to moderate. Abstract: Purpose: Administration of three doses of Pfizer-BioNTech BNT162b2 COVID-19 mRNA vaccine was completed in Japan in the spring of 2022. This study aimed to evaluate the antibody responses, and kinetics of three doses of vaccine in healthcare workers (HCWs). Patients and methods: We conducted a longitudinal cohort study with HCWs, who had no history of COVID-19 or serologic evidence of SARS-CoV-2 infection, from a single hospital. Immunoglobulin G (IgG) titers of anti-SARS-CoV-2 spike protein (SP) and nucleocapsid protein (NP) titers were measured using an automated chemiluminescent enzyme immunoassay system. Results: A total of 636 HCWs participated in the study. The anti-SP IgG titers decreased slowly after the second dose of the BNT162b2 vaccine in all participants, and robust antibody response was observed after the third dose of the vaccine. The peak anti-SP IgG titer after the third dose was approximately 4.1-fold higher than that after the first and second doses, and the rate of decrease in the anti-SP IgG titer after the third dose was significantly more gradual, than that after the second dose. After the second dose of vaccine, the antibody response was weaker in older participants than in younger participants, and in males than in females respectively, whereas the response to the third dose of vaccine did not differ significantly by sex or age. Adverse events following immunization were generally mild to moderate. Conclusion: The third dose of the BNT162b2 vaccine induced a significant and sustained increase in anti-SP IgG titers, and was generally safe and well-tolerated.